Cardiovascular risk factor prevalence in students by gender and blood pressure level - O. A. Kamyshansky; S. T. Ignatova; G. O. Treneva; I. V. Shchenyatskaya; A. A. Ryabov; L. B. Lazebnik (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of selected cardiovascular risk factors in young people with arterial hypertension (AH) and high normal blood pressure (HNBP), to clarify primary AH prevention strategies.Material and methods. The study included 2280 students (1041 men, 1239 women) aged 18-25 years. Body mass index and waist circumference were measured to identify obesity type. Prevalence of smoking, lipid, fiber, alcohol consumption patterns, and alcohol dependence severity were assessed by questionnaire survey.Results. AH was diagnosed in 10,6 % of the students, HNBP - in 12,4 %, optimal BP - in 41 %, and normal BP -in 36 %. Abdominal obesity was 3 times more common in women than in men. For men, smoking, alcohol drinking, and cholesterol-rich food consumption were typical.Conclusion. In male students, AH prevalence was 3 times higher, and HNBP prevalence - more than 4 times higher than in female students. Three or four risk factors were identified only in individuals with AH or HNBP, more often in females, due to higher prevalence of increased body weight among women.